Factors contributing to insufficient scientific writing skills among junior high school teachers - Virman, Virman; Pieter, Jan; G. D. Lasmono, Paulus; Nainggolan, Jonner; Abraham, Abraham (UIN Raden Mas Said Surakarta, 2024)
For teachers and educators, one self-competency that must be developed is enhancing research and scientific paper dissemination. This study aims to determine the abilities and obstacles experienced by teachers in writing scientific papers. Implementing a sequential research design, this research adopts both quantitative and qualitative analysis. Twenty-seven teachers contributed as participants and gathered data through questionnaires, which were analyzed quantitatively, and semi-structured interviews which were analyzed qualitatively using thematic analysis. The results showed that SMP Negeri 6 Kota Jayapura teachers still face challenges in writing scientific papers. The scores for each issue are as follows: lack of understanding of publication writing guidelines is the most crucial issue with 24.59%. The second highest issue is the minimal time available to teachers, scoring 19.67%. The third highest issue is low teacher motivation, scoring 11.03%. The fourth highest issues are the lack of information on article writing, the prevalence of scientific paper writing services, and teachers' inability to operate computers, scoring 9.83%. The fifth highest issues are the lack of teacher skills in finding references, non-compliance of teachers' journals with writing guidelines, and limited references needed for writing. In conclusion, the three most dominant factors contributing to insufficient writing ability are the lack of scientific writing knowledge, lack of writing time and administrative demand, and low writing motivation. The research findings offer valuable insight both practically and theoretically. In fostering the related issues, training and ongoing support are crucial for developing and maintaining high standards of scientific writing among educators.